Harvesting Bioelectricity from Microbial Fuel Cells (MFCs) Powered by Electroactive Microbes - Yohanna Anisa Indriyani; Iman Rusmana; Syaiful Anwar; Gunawan Djajakirana; Dwi Andreas Santosa (The University of Lampung, 2023)
The application of microbial fuel cells is still facing some challenges due to its low power output and high internal resistance. It is desirable to obtain a stable and consistent power output from an MFC to support practical real-world applications. Five electroactive bacteria (isolate LGf1, LGf11, LGf15, LGf20, and LGf22) isolated from the sediment of Waduk Saguling were exploited as the potential anodic biocatalyst for MFC, and the performance of these MFCs were studied in terms of voltage generation (open and close circuit), power density and the losses (polarization technique), and efficiencies (coulombic and energy). MFC biocatalyst by isolate LGf11 performed the best electrochemical performances, including highest OCV (open circuit voltage) value (804 mV) and power output (0.043 W/m2), lowest ohmic resistance (475 Ω), and highest coulombic efficiency (75.79%) and energy efficiency (88.36%) among all anodic biocatalysts. Nevertheless, all the five isolates were potential to be exploited as active biocatalyst for MFC due to their high OCV values and the stability of voltage generations, both in open circuit and close circuit mode. The development of system configuration and the use of more suitable substrate for different electroactive microbes in order to harvest more power output was recommended for further study. Utilization of these potential microbes for other applications in MFC (such as wastewater treatment etc.) was also suggested for further research. Keywords: Bio-electrochemical system, Biofuel, Efficiency, Electro-microbiology, Power output